Two contemporaneous morphs of fossil Chanos Lacepède, 1803 (Gonorynchiformes, Chanidae) from Paleocene (Danian) outcrops near Palenque (Mexico) revealed by geometric morphometrics indicate conservatism in milkfishes after the K/Pg boundary - Alberto Guadarrama; Kleyton M Cantalice (PLoS ONE, 2025)
We described chanid material from the Paleocene (Danian) localities of División del Norte and Belisario Domínguez near the archeological site of Palenque, Chiapas State, southeastern Mexico. The parsimony-based morphological phylogeny indicates that the specimens are closely related to the extant milkfish, Chanos chanos (Teleostei, Ostariophysi), and the comparative anatomy reveals a remarkable qualitative similarity of almost every visible bone. Among the synapomorphies for the genus Chanos, is a pleurostyle or caudal complex, which is missing in all other chanid fossils. Extant milkfish are highly variable in meristic and morphometric traits, and we found a signal for quantitative variation with geometric morphometrics tools in the fossil sample. We first dealt with post-mortem body torsion and missing landmarks. The main analysis shows a pattern of two forms present in both localities. A group of specimens shows a bigger head and deeper body than the slender and smaller head of the rest, implying that two types of milkfish coexisted in time and space. We tested for allometry and explored scenarios that can explain the patterns, such as sexual dimorphism or two sympatric and closely related species for the morphotypes, and differential resource utilization for the jaw, head, and depth variations. Furthermore, we argue that, alongside the morphological stasis, Chanos has conserved the life history trait of fry migration towards near-shore nurseries through protracted time (~63mybp). We infer the fish were juvenile, and the paleontological assemblage and taphonomy suggest that the localities exhibit the influence of both marine and transitional environments.